2016
DOI: 10.18632/oncotarget.7282
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive value of tumor-infiltrating lymphocytes for clinical therapeutic research in patients with non-small cell lung cancer

Abstract: BackgroundPrevious preclinical and clinical studies have shown that levels of tumor-infiltrating lymphocytes (TILs) significantly correlated with prognosis in non-small cell lung cancer (NSCLC), and survival after therapy; however, this finding remains controversial. We performed a meta-analysis, to evaluate, systematically, the clinical utilization of TIL subtypes in patients with NSCLC.MethodsThe PubMed, ISI Web of Science, EMBASE, and Cochrane Library databases were searched to identify relevant studies. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
113
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(136 citation statements)
references
References 57 publications
5
113
3
1
Order By: Relevance
“…CD4 + T cells were only associated with overall survival when assessed in the tumor stroma rather than the tumor cell nests, while FOXP3 + T regs in the tumor stroma were associated with poorer progression free survival [129]. Sixteen of these studies, along with an additional eight studies, were included in a meta-analysis by Zeng et al [133]. These authors concluded that high levels of CD8 + , CD3 + and CD4 + TILs had prognostic significance for both overall survival and recurrence [133].…”
Section: Tils In Non-small Cell Lung Carcinomamentioning
confidence: 99%
See 2 more Smart Citations
“…CD4 + T cells were only associated with overall survival when assessed in the tumor stroma rather than the tumor cell nests, while FOXP3 + T regs in the tumor stroma were associated with poorer progression free survival [129]. Sixteen of these studies, along with an additional eight studies, were included in a meta-analysis by Zeng et al [133]. These authors concluded that high levels of CD8 + , CD3 + and CD4 + TILs had prognostic significance for both overall survival and recurrence [133].…”
Section: Tils In Non-small Cell Lung Carcinomamentioning
confidence: 99%
“…Sixteen of these studies, along with an additional eight studies, were included in a meta-analysis by Zeng et al [133]. These authors concluded that high levels of CD8 + , CD3 + and CD4 + TILs had prognostic significance for both overall survival and recurrence [133]. Of note is the moderate to significant heterogeneity identified in both of these meta-analyses, as well as the retrospective nature of the included studies, many of which had incomplete data with regard to important prognostic factors [129,133].…”
Section: Tils In Non-small Cell Lung Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other components of the tumor microenvironment, such as tumor-infiltrating lymphocytes (TIL), critically contribute to tumor biology and therapeutic response to ICI (24), suggesting that predictive biomarkers aimed at personalized therapy can be obtained by a coordinated multiparametric definition of the immune contexture (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…Both of these studies acknowledged that the relative significance of CD8 T cell infiltration in the center of the tumor versus that of the tumor margin is not yet clear [14, 17]. In addition, associations between CD8 T cell infiltration and survival have varied across multiple studies of human NSCLC [3, 15, 1824]. …”
Section: Introductionmentioning
confidence: 99%